Trend of Variation in Fibre Length in Bamboos - Pattanath, P. G. (Indian Forester, 1972)
The trend in variation of fibre length within a culm has been studied for twelve different species of bamhoos. While the fibre length in the lower portion of the culms is generally greater than levels, the pattern of variation is not the same in different species. Fibre length also does not show any consistent relationship with internode length in the species investigated.